Doped microcrystalline silicon as front surface field layer in bifacial silicon heterojunction solar cells. (September 2017) - Sergeev, Oleg; Neumüller, Alex; Shutsko, Ivan; Vehse, Martin; Agert, Carsten
Abstract: In silicon heterojunction solar cells with thin intrinsic layers (SHJ) based on n-type silicon wafers, it is common to use a p-doped front emitter and back surface field (n-layer). In this study, SHJ cells were developed and investigated in front surface field (FSF) configuration with a n-doped layer at the front side. The electrical and optical properties of the FSF play a crucial role in cell operation. Ideally, the FSF demonstrates low light absorption, efficient extraction of electrons to contacts, as well as chemical and electrical passivation. The goal of this work is to study the physical properties of n-doped microcrystalline silicon thin films and apply them as the FSF layer in SHJ solar cells. We demonstrate promising results in such SHJ solar cells with short-current density of 2.9 mA/cm² higher compared to reference cells with amorphous FSF.